PRIDE AND DIGNITY OF ADOLPHUS SIMPSON AS REVEALED IN POE’S THE SPECTACLES - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2023)
This research presents a description of the character and personality of Simpson in